2006
DOI: 10.1089/aid.2006.22.953
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human T Cell Lymphotropic Virus Type 1 (HTLV-1) Subtypes in Brazil: Genetic Characterization of LTR and Tax Region

Abstract: We report the molecular and epidemiological characterization of 128 human T cell lymphotropic virus type 1 (HTLV-1) isolates from Brazilian patients with different clinical manifestations of the infection. Thirty-two percent of the patients were asymptomatic, 44% had HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), and 23% had adult T cell leukemia/lymphoma (ATLL). Phylogenetic analysis performed using part of the LTR region of the viral genome revealed that all Brazilian isolates belonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
6
25
0
7
Order By: Relevance
“…10 Corroborating these data, another study from Sã o Paulo showed the same pattern of mutations and a lack of association between the tax genotype and disease progression. In addition to some regions of Brazil being considered endemic for HTLV-1 infection, 4 Brazil is considered epidemic for HIV/AIDS, with prevalence rates of 0.3% to 0.6% 13 ; as a result, HIV/HTLV-1 coinfection has been described in this country, with prevalence rates varying according to the geographic area.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…10 Corroborating these data, another study from Sã o Paulo showed the same pattern of mutations and a lack of association between the tax genotype and disease progression. In addition to some regions of Brazil being considered endemic for HTLV-1 infection, 4 Brazil is considered epidemic for HIV/AIDS, with prevalence rates of 0.3% to 0.6% 13 ; as a result, HIV/HTLV-1 coinfection has been described in this country, with prevalence rates varying according to the geographic area.…”
mentioning
confidence: 87%
“…In fact, this subgroup was detected in some individuals from southeastern Brazil. 10 On the basis of the molecular analysis of the tax gene, HTLV-1 strains were classified into two genotypes, taxA and taxB, whose association with clinical disease was suggested.…”
mentioning
confidence: 99%
“…Clinical Diagnostic Inc. Raritan, �ew Jersey, USA) were confirmed and discriminated between HTLV-1 and HTLV-2 using Western Blot (HTLV Blot 2.4; Genelabs, Singapore). Polymerase Chain Reaction (PCR) analysis was performed in samples with undetermined results according to the technique described elsewhere 13 . The diagnosis of HAM/TSP was determined according to the WHO guidelines 28 A full ophthalmologic examination was performed, including visual acuity measurement by Snellen eye chart, with optical correction, optical motility, applanation tonometry, biomicroscopy of the anterior and posterior chambers, binocular indirect ophthalmoscopy with or without depression, in both eyes and intraocular pressure.…”
Section: Studymentioning
confidence: 99%
“…The subtypes do not vary in pathogenicity and most likely refl ect the geographical origins and migrations of ancient populations [21][22][23] . In addition, genomic sequencing has confi rmed the transmission of HTLV-1 from infected spouses to uninfected spouses by revealing identical sequences in seropositive individuals and those spouses who seroconverted 24 .…”
Section: Introductionmentioning
confidence: 99%